Procedures in Translation Taking Place in the Translation of English Medical Terms with Reference to Clinical (e-Journal of Linguistics, 2020)
This study aimed at finding out the translation procedures whichwere applied in the translation of English Medical Terms withreference to English Medical Book entitled Clinical Biochemistry4th and its translation version in Indonesian entitled Biokimia KlinisEdisi 4. The analysis of translation the procedure was based on atheory proposed by Newmark (1988) by which eighteen proceduresare mentioned. Moreover, this study applied a descriptivequalitative approach. In collecting data, this study applied anobservation method by reading Clinical Biochemistry and itstranslation Biokimia Klinis comprehensively to collect the requireddata i.e. the medical terms and their translation. Furthermore, thisstudy applied descriptive qualitative method in terms of analyzingdata. The method was implemented by providing an explanation ofthe translation procedures. Moreover, the formal and informalmethods were implemented in presenting the data. The formalmethod is indicated by the use of the table where the term and itstranslation were placed and differed into SL and TL. The informalmethod refers to the use of a descriptive explanation regarding thetranslation procedure. After the identification process, it was foundsome procedures were applied, i.e. transference, naturalization,literal, and descriptive equivalent. The dominant procedure appliedwas literal procedure. The contrary, descriptive equivalent was theleast applied procedure. Based on the result, it can be confirmedthat there was an attempt by translator in maintaining the SL wordsrather than considering TL words as the translation
Keywords: Translation; English Medical Terms; Translation Procedures